Relationship Between Reading Distance, Reading Duration, and Smartphone Usage Duration with the Incidence of Refractive Errors Among Students at SMAN 1 Praya - Al Rasyid, Lalu Zainul; Subekti, Sri; Mahayani, Ida Ayu Made; Prabawa, Dewa Gede Benny Raharja (Jurnal Biologi Tropis, 2025)
Refractive errors occur when light entering the eye cannot be properly focused, resulting in blurry or unclear vision. This study aims to determine the relationship between reading distance, reading duration, and smartphone usage duration with the incidence of refractive errors among students at SMAN 1 Praya. Using a cross-sectional design, this quantitative study involved 103 respondents selected through stratified random sampling. Data were analyzed using univariate and bivariate methods with the Chi-square test. The results showed significant relationships between reading distance (p-value = 0.001), reading duration (p-value = 0.001), and smartphone usage duration (p-value = 0.001) with the incidence of refractive errors. In conclusion, reading distance, reading duration, and smartphone usage duration are significantly associated with the incidence of refractive errors among students at SMAN 1 Praya. This research can be expanded by incorporating additional independent variables, such as outdoor activities, sleep patterns, or genetic factors, to offer a more thorough understanding of the risk factors for refractive errors.